Assessment of urban forest species preference and nursery use practice in Pokhara Metropolitan City - Acharya, Madan; Subedi, Bibek; Subedi, Sagar (Banko Janakari, 2023)
Pokhara is one of the rapidly urbanizing cities with declining trees and green spaces. It has become imperative to develop effective plans and strategies to maintain greenery in the city. There is little knowledge about the individual choice of urban tree species and how it shapes up the urban green spaces. This study was conducted in the Ward 17 of the Pokhara Metropolitan City to assess the people’s preferences and factors influencing their choices. Data collection was done through nursery survey (n=15), household survey (n=60), and site observation (n=12). The observed sites were parks, religious sites and streets of Ward-17 of the Pokhara Metropolitan City. Majority of the household were found to be practicing home gardens with exotic species which were more preferred than the indigenous ones. Altogether, 15 major species were recorded from the households, with Dhupi (Juniperus indica) being the most frequent species followed by Guava (Psidium guajava). A total of 48 tree species were recorded during site observation, with a maximum frequency of Sissoo (Dalbergia sissoo). Among the six major factors for species selection, use and benefits derived from the species were detected as the most responsible ones. Nurseries provide seedlings mostly for individual purposes; however, financial and technical assistance should be provided to all the interested households with emphasis on the preferred type of species required for further development of urban forestry in the Pokhara Metropolitan City.